Impact of two disinfectants on detachment of Enterococcus faecalis from polythene in aquatic microcosm - Djimeli, C. Lontsi; Arfao, A. Tamsa; Rossi, V; Nsulem, N; Raspal, V; Bricheux, G; Nola, M; Sime-Ngando, T. (Research in Biotechnology, 2016)
After cell adhesion processes in microcosm, the impact of sodium hypochlorite (NaOCl) and hydrogen peroxide (H2O2) on the detachment of Enterococcus faecalis from polythene fragments immersed in water under stationary and dynamic conditions was assessed. The abundance of planktonic cells was also evaluated. The density of E. faecalis adhered in absence of disinfectant fluctuated between 2 and 4 units (Log CFU/cm2). After living in disinfected water, the density of E. faecalis remained adhered to polythene sometimes reached 2 units (Log CFU/Cm2). This highest abundance of cells remained adhered was recorded with cells coming from the lag, exponential and stationary growth phases in water treated with 0.5‰ NaOCl. In H2O2 disinfected water, the highest value was recorded at all cells growth phases with 5‰ H2O2 concentration. Adhered E. faecalis cells have been sometimes completely or partially decimated respectively by NaOCl and H2O2 treated water. Considering separately each experimental condition, it was noted that increasing the concentration of disinfectant caused a significant decrease (P≤0.01) in abundance of cells stay adhered after living in water disinfected by the two disinfectants. Changes in disinfectant concentrations in different experimental conditions had an impact on the detachment of E. faecalis cells from the substrates.